Fucoidan-coated coral-like Pt nanoparticles for computed tomography-guided highly enhanced synergistic anticancer effect against drug-resistant breast cancer cells. Issue 32 (5th August 2019) - Kang, Seounghun; Kang, Kyunglee; Chae, Ari; Kim, Young-Kwan; Jang, Hongje; Min, Dal-Hee
Abstract : The one-pot synthesis with surface modification of Pt nanoparticle through bioactive polymer, fucoidan, were applied to achieve efficient combination therapy of MDR breast cancer cells. Abstract : Chemotherapy, the most commonly applied cancer treatment, often causes unexpected failure due to multidrug resistance (MDR). To overcome MDR, we have designed a platform to realize a combinational synergistic effect of a natural bioactive product (fucoidan), anticancer small compound (doxorubicin), and photothermal nanocarrier (Pt nanoparticle) to treat drug-resistant breast cancer cells. Especially, fucoidan, a sulfated, polysaccharide-structured, therapeutic biopolymer, has been recently recognized as a potential anticancer compound; however, its cancer-inhibiting efficacy has been regarded as low owing to its insufficient level in serum following its conventional oral ingestion. To enhance its potency, fucoidan was applied as a biocompatible surfactant and surface-coating biopolymer in nanocarrier synthesis to manufacture coral-like, fucoidan-coated Pt nanoparticles with a rough surface morphology by a one-pot method. As a result, the biological-thermo-chemo trimodal combination treatment showed excellent therapeutic efficiency against the MDR breast cancer cell MCF-7 ADR both in vitro and in vivo, and the computed tomography contrast effect was also confirmed from the constituent element Pt. Beyond universal application in drug delivery and photothermal therapy, the present approach of applying a MDR modulating/anticancer natural product from nanoparticle synthesis to theranostics will contribute greatly to maximizing their potential through interdisciplinary convergence in the near future.